1984
DOI: 10.1136/bmj.289.6449.896
|View full text |Cite
|
Sign up to set email alerts
|

Cervical smear histories of 500 women with invasive cervical cancer in Yorkshire.

Abstract: The smear histories of 312 women with cancer of the cervix have been determined. Eighty nine women had had at least one negative smear reported in the 10 years before a diagnosis of cancer and 14 had had more than one negative smear. Fifty six of the 89 women had had a negative smear in the three years preceding the diagnosis of cancer. The highest number of negative smears (61) reported was among the 115 women aged under 45. Fifty eight slides reported as negative were submitted to independent review; 13 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
2

Year Published

1989
1989
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 18 publications
1
54
0
2
Order By: Relevance
“…This has been linked largely to good population coverage (Boyes et al 1961, MacGregor et al 1985. Moreover, it is argued that a high proportion of women with cervical cancer have never had a smear test (Paterson et al 1982), and further, that women who are screened have a low incidence of cervical cancer (Chamberlain 1984). Consequently, General Practice in the NHS: the 1990 Contract (DoH 1989) recommended that women aged between 20 and 60 in Scotland (20 and 64 in England and Wales) should be offered cervical cytology, and established requirements within general practice to incorporate screening targets for cervical disease, linked to remuneration.…”
Section: Prevention Discourse and Cervical Screeningmentioning
confidence: 99%
“…This has been linked largely to good population coverage (Boyes et al 1961, MacGregor et al 1985. Moreover, it is argued that a high proportion of women with cervical cancer have never had a smear test (Paterson et al 1982), and further, that women who are screened have a low incidence of cervical cancer (Chamberlain 1984). Consequently, General Practice in the NHS: the 1990 Contract (DoH 1989) recommended that women aged between 20 and 60 in Scotland (20 and 64 in England and Wales) should be offered cervical cytology, and established requirements within general practice to incorporate screening targets for cervical disease, linked to remuneration.…”
Section: Prevention Discourse and Cervical Screeningmentioning
confidence: 99%
“…There was less variation between the smears from cases and from controls in the percentages of unsatisfactory, which varied between 13-25% among smears from cases and 15-29% among smears from controls. (Mitchell et al, 1988) to 64% (Attwood et al, 1985) previously reported in the predominantly small series of patients with invasive cervical cancer for whom the previous negative smears have been reviewed (Rylander, 1977;Gad & Koch, 1978;Berkowitz et al, 1979;Berkeley et al, 1980;Holman et al, 1981;Morell et al, 1982;Walker et al, 1983: Paterson et al, 1984Gay et al, 1985;Attwood et al, 1985;Graff et al, 1987;Mitchell et al, 1988;Mitchell et al, 1990).…”
mentioning
confidence: 99%
“…[13][14][15][16] Nevertheless, cervical cancer screening programmes occasionally encounter women with ICC that have followed the screening guidelines after a normal or a mild abnormal result. [17][18][19][20][21][22][23][24] There is thus a potential for improving the screening programme. Women with a normal Pap smear have a low risk of subsequently developing ICC [25][26][27][28][29] and their incidence rate comprises the improvement potential of the screening programme, and the reference for evaluating guidelines for women with mild abnormalities.…”
mentioning
confidence: 99%